2007
DOI: 10.1111/j.1520-037x.2007.06619.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease Knowledge, Medication Adherence, and Barriers to Preventive Action in a Minority Population

Abstract: Lack of knowledge and awareness of cardiovascular disease may contribute to disproportionately higher risk in minorities. The authors studied minorities in Harlem, New York (N=214), to evaluate knowledge and preventive behaviors. More than half of the participants did not know optimal blood pressure (BP) (52%) and cholesterol (60%) goals. Lack of health insurance (odds ratio, 2.1; 95% confidence interval, 1.0-4.5) and less than a high school education (odds ratio, 2.0;95% confidence interval, 1.02-3.87) were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 22 publications
2
34
1
2
Order By: Relevance
“…This thesis has also been substantiated by Di Chiara et al [23], who showed a correlation between a lower level of education and prevalence of marked abdominal obesity, and microalbuminuria. Mochari et al [24] reported that low education and lack of insurance is associated with a lower level of knowledge regarding the optimal values of blood pressure and blood cholesterol concentration, particularly in patients below 45 years of age. A review of literature on the education of patients with cardiovascular diseases shows that Canadian researchers advocate focusing on a group with a low level of health literacy and cognitive skills [25].…”
Section: Discussionmentioning
confidence: 99%
“…This thesis has also been substantiated by Di Chiara et al [23], who showed a correlation between a lower level of education and prevalence of marked abdominal obesity, and microalbuminuria. Mochari et al [24] reported that low education and lack of insurance is associated with a lower level of knowledge regarding the optimal values of blood pressure and blood cholesterol concentration, particularly in patients below 45 years of age. A review of literature on the education of patients with cardiovascular diseases shows that Canadian researchers advocate focusing on a group with a low level of health literacy and cognitive skills [25].…”
Section: Discussionmentioning
confidence: 99%
“…We considered additional clinical and sociodemographic characteristics known to be associated with medication adherence. [4][5][6][7][8][9][10][11][12] Clinical characteristics included diagnoses of hypertension, hyperlipidemia, or hypertension and hyperlipidemia, as well as diabetes (diagnosed vs. not diagnosed). Sociodemographic characteristics included age, race (non-Hispanic white vs. minority), gender (male vs. female), marital status (married or living with partner vs. all other statuses), education (high school graduate or less than high school vs. any college), and employment status (employed vs. not employed).…”
Section: What Is Already Known About This Subjectmentioning
confidence: 99%
“…Sociodemographic risk factors, such as minority race, low health literacy, and lack of access, among others, are known to be associated with medication nonadherence. [4][5][6][7][8][9][10][11][12] A systematic literature review conducted by Gellad et al (2011) identified barriers to medication adherence, including patient-related factors (e.g, disease-related knowledge, health literacy, and cognitive function); drug-related factors (e.g., adverse effects and polypharmacy); and other factors such as the patent-provider relationships and various challenges to obtaining medications. 13 These barriers include the cost of medications and regimen complexity (i.e., the number of medications taken or the frequency of times per day).…”
mentioning
confidence: 99%
“…Having less than a high school education has been associated with lack of understanding about optimal BP and medication nonadherence. 4,6 Therefore, a dichotomized measure of patient-reported educational…”
Section: Employment Status and Educational Attainmentmentioning
confidence: 99%
“…2 Reasons for medication nonadherence in CVD risk reduction are often multifactorial and include health system factors (eg, poor patient-provider communication, lack of access), comorbid health conditions (eg, depression, asymptomatic conditions), patient factors (eg, cognitive impairment), therapy (eg, side effects), and socioeconomic characteristics (eg, low literacy, cost, race). [2][3][4][5][6][7][8][9][10] Recognizing and modifying barriers to proper medication adherence is a critical first step to improving rates of adherence in patients with CVD.…”
mentioning
confidence: 99%